PERAN ORANG KUAT LOKAL DALAM KEMENANGAN PASANGAN EDY RAHMAYADI-MUSA RAJECKSHAH PADA PILGUBSU 2018 - Ramadhan, Mhd Fhitra; Ali Azhar, Muhammad; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2021)
This research seeks to find out the role of youth figures to help candidate in North Sumatra Election 2018. This study was designed using local strongmen theory by Joel. S. Migdal to find out the power and influence youth figures in helping the victory of candidate pairs at the time of the election. The descriptive qualitative methodology, which incorporated both primary and secondary data collecting methods, was used in this study because it portrays the role of local strongmen in the North Sumatra Election 2018. The results: first, the local strongman used the influence and experience he gained to consolidate, socialize, and form networks. Second, the type of networks that local strongman have when he helping the candidates, social networks and political networks. Local strongmen form social relationships with the leadership of community organizations through their influence, local strongman form political relationships with candidate spouses. Through the experience you have. Keywords: Elections, Local Strongmen, Network, Politics.